How do investors view information disclosure quality rating?: The effect of FNFI on corporate investment efficiency. Issue 2 (5th June 2017) - Tan, Youchao; Liu, Yuyu
Abstract : Purpose: Following Cheng et al. (2012) and Tan et al. (2015), this paper aims to investigate how does the forward-looking information disclosure quality affect the investors' decisions and then the investment efficiency. Design/methodology/approach: The authors obtain the information disclosure quality rating data from the official website of the Shenzhen Stock Exchange (SZSE), and firm financial information is mainly from the China Center for Economic Research (CCER) and China Stock Market and Accounting Research Database (CSMAR). The authors choose firms that publicly traded on the SZSE during the period from 2004 to 2010, and the final sample consists of 2, 415 firm-year observations for 345 unique firms. Findings: The authors find that a firm with a high information disclosure quality rating is trusted by investors more. Forward-looking non-financial information (FNFI) disclosure alleviates financial constraints and improves investment efficiency, including alleviating underinvestment and preventing overinvestment to a larger extent for firms with high information disclosure quality rating, especially for the firms rated A (excellent) or B (good) every year since 2001, when the rating began. Moreover, this study proves that investors trust the firms rated high more but do not guard against the firms rated low enough. Research limitations/implications: The authors only considered the quantity of FNFI disclosed by firms and ignored other characteristics of FNFI. Limited by the data of information disclosure quality rating, the research sample is just from the SZSE. Originality/value: This paper extends the research of Cheng et al. (2012) and Tan et al. (2015) to show that one of the reasons behind the extant mix results of the relationship between FNF disclosure and investment efficiency is different information disclosure quality. High-quality FNFI disclosure can alleviate underinvestment and prevent overinvestment at same time.